2008
DOI: 10.1680/adcr.2008.20.1.13
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of diatomite blend in natural pozzolan-blended cements

Abstract: The aim of this study was to examine usability of diatomite, a natural amorphous and porous raw material, as an additional blend in an effort to improve the performances of natural pozzolan-blended cements. To this aim, varying proportions of pozzolan, diatomite and pozzolan-diatomite-blended cements were prepared and chemical, physical, mechanical, mineralogical and microstructural tests were applied to the resulting cements. The test results indicated that diatomite blend may be effective in improving pozzol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The best compressive strength values at later ages were obtained using the diatomaceous earth with the highest amorphous silica content. The late compressive strength of most pastes modified with diatomite was improved compared to that of reference cement paste which agrees with previously published reports [ 43 , 51 , 52 ].…”
Section: Introductionsupporting
confidence: 91%
“…The best compressive strength values at later ages were obtained using the diatomaceous earth with the highest amorphous silica content. The late compressive strength of most pastes modified with diatomite was improved compared to that of reference cement paste which agrees with previously published reports [ 43 , 51 , 52 ].…”
Section: Introductionsupporting
confidence: 91%
“…Nowadays, it is common to use diatomites in areas related to cement, concrete, and high-performance mortars. Yilmaz [ 1 , 2 ] and Janotka et al [ 3 ] consider diatomites as amorphous and porous materials, and on this basis they have focused their research on the hydraulic effect produced by the standardized mixture of natural and calcined diatomites with Portland cement in varying proportions, resulting in an improvement in pozzolanic reactivity, a decrease in setting time, a reduction in the alkali, and a consequent increase in the normal mechanical strength of the mortars. Along the same lines, Mota and Chagas [ 4 ] as well as Paiva et al [ 5 ] found that reducing the size of diatomite particles to 10 μm significantly increased the surface area, porosity, hydraulic activity, and mechanical strength of the diatomite-portlandite interface.…”
Section: Introductionmentioning
confidence: 99%
“…However, as a replacement for 5% of Portland cement, it allows to obtain mechanical properties similar to the reference sample while improving the sulfate resistance of mortars. Yilmaz [ 31 ] reported that after both 28 and 360 days of hydration, the compressive of mortars containing up to 10% of diatomite blended with OPC was comparable to the reference sample, while for 20% of the substitution, a 24% decrease was observed. The water demand of the binder increased from 28.4 wt.% to 30.0–37.0 wt.% for 10–20% of the addition, while the initial setting time was shortened by 10–15 min.…”
Section: Introductionmentioning
confidence: 99%